Analisis Potensi dan Masalah Desa Berbasis Sistem Informasi Geografis (Studi Kasus: Desa Gemeksekti, Kabupaten Kebumen) - Ziyadatul Hikmah (Faculty of Forestry Universitas Gadjah Mada, 2022)
Gemeksekti village is one of the villages left behind in Kebumen Regency that has a wealth of natural resources and local cultural heritage but cannot be developed to its fullest. The existing potential had not been systematically identified due to limited human resources for village development, uneven education, low institutional capacity development, and access to the home industry market that had not been optimal. The purpose of this research was to map the potential of Gemeksekti Village, Kebumen Subdistrict, Kebumen Regency and know its distribution based on Geographic Information System (SIG). The method of data collection used was by the method of literature study, interviews directly to gemeksekti village devices and field observations. Research data analysis techniques were carried out descriptively quantitative and spatial analysis with overlay analysis method in ArcGIS 10.5 and generated a map of the potential distribution and problems of Gemeksekti Village. Gemeksekti Village potential and problems that were successfully mapped using Geographic Information System (SIG) included the potential of natural resources, human resource potential and potential facilities owned by the village; and village problems included aspects of sanitation, health and environment.